The association between snacking habits and the incidence of diarrhoea among school-aged children at SD Negeri 060834 Medan Petisah - Gea, Lestin; Hartono, Hartono; Ginting, Rapael (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2025)
Background: Diarrhoea remains a significant health concern among school-aged children, with snacking habits playing a potential role in its occurrence. Aim: This study aimed to examine the relationship between snacking habits (frequency, type, and consumption practices) and the incidence of diarrhoea among primary school students at SDN 060834 Medan Petisah. Methods: A cross-sectional study was conducted with 56 students in grades IV–VI. Data were collected using a structured questionnaire assessing snacking habits and diarrhoea incidence. Statistical analysis employed chi-square tests to determine associations. Results: The majority of respondents (60.7%) reported frequent snacking, with 58.9% exhibiting healthy snacking practices. No significant association was found between the frequency (p=0.549) or type (p=0.122) of snacks consumed and diarrhoea. However, unhealthy snacking practices showed a significant association with diarrhoea incidence (p=0.001), with 64.3% of students engaging in unhealthy practices experiencing diarrhoea. Conclusion: Unhealthy snacking practices significantly increase the risk of diarrhoea among schoolchildren. Interventions promoting hygienic and nutritious snacking habits are essential to reduce diarrhoea prevalence in this population.